Fabrication of nanoscale speckle using broad ion beam milling on polymers for deformation analysis. Issue 4 (July 2016) - Wang, Qinghua; Kishimoto, Satoshi; Tanaka, Yoshihisa; Naito, Kimiyoshi
Abstract: We first report a fabrication technique of nanoscale speckle patterns on polymers using broad ion beam milling. The proposed technique is simple and low-cost to produce speckles ranging from dozens of nanometers to less than three micrometers in a large area of several millimeters. Random patterns were successfully produced with an argon (Ar) ion beam on the surfaces of four kinds of polymers: the epoxy matrix of carbon fiber reinforced plastic, polyester, polyvinyl formal-acetal, and polyimide. The speckle morphologies slightly vary with different polymers. The fabricated speckle patterns have good time stability and are promising to be used to measure the nanoscale deformations of polymers using the digital image correlation method. Highlights: A fabrication technique of nanoscale speckle using broad ion milling was proposed. It is simple and low-cost to fabricate nanoscale speckle on polymers in a large area. Speckle morphologies under different milling times and tilt angles on different polymers were studied. The fabricated speckle with good time stability is useful for deformation measurement.